Efficacy and safety of ultrasound-guided pulsed radiofrequency in the treatment of the ophthalmic branch of postherpetic trigeminal neuralgia - Li, Fubo; Gong, Gege; Zhang, Yue; Ou, Cehua (Frontiers in Neurology, 2024)
Objective To investigate the efficacy and safety of ultrasound-guided pulsed radiofrequency (PRF) targeting the supraorbital nerve for treating the ophthalmic branch of postherpetic trigeminal neuralgia. Methods A retrospective cohort study was conducted involving patients who presented at the Department of Pain, Affiliated Hospital of Southwest Medical University from January 2015 to January 2022. The patients were diagnosed with the first branch of postherpetic trigeminal neuralgia. In total, 63 patients were included based on the inclusion and exclusion criteria. The patients were divided into the following two groups based on the treatment method used: the nerve block (NB) group (n = 32) and the PRF + NB group (radiofrequency group, n = 31). The visual analog scale (VAS) score, Pittsburgh Sleep Quality Index (PSQI) score, and pregabalin dose were compared between the two groups before treatment, 1 week after the procedure, and 1, 3, and 6 months post-procedure, and the complications, such as local infection, local hematoma, and decreased visual acuity, were monitored post-treatment. Results No significant difference was found in terms of pretreatment age, sex, course of disease, preoperative VAS score, preoperative PSQI score, and preoperative pregabalin dose between the two groups (P > 0.05). The postoperative VAS score, PSQI score, and pregabalin dose were significantly decreased in both groups. Furthermore, significant differences were found between the two groups at each preoperative and postoperative time point (P < 0.05). The VAS score was lower in the radiofrequency group than in the NB group at 1, 3, and 6 months, and the difference was statistically significant (P < 0.05). The PSQI score was lower in the radiofrequency group than in the NB group at 1 week, 1, 3, and 6 months post-procedure, and the difference was statistically significant (P < 0.05). The dose of pregabalin was lower in the radiofrequency group than in the NB group at 1 week, 1, 3, and 6 months post-procedure, and the difference was statistically significant at 3 and 6 months (P < 0.05). After 6 months of treatment, the excellent rate of VAS score in the radiofrequency group was 70.96%, and the overall effective rate was 90.32%, which was higher than that in the NB group. The difference in the efficacy was statistically significant (P < 0.05). Conclusion PRF targeting the supraorbital nerve can effectively control the pain in the first branch of the trigeminal nerve after herpes, enhance sleep quality, and reduce the dose of pregabalin. Thus, this study shows that PRF is safe under ultrasound guidance and is worthy of clinical application.